Is transphyseal intramedullary fixation of the distal radius in pediatric fractures a safe procedure? An MRI study - Giordano, Marco; Florio, Michela; Careri, Silvia; Cirillo, Marco; Aulisa, Angelo Gabriele; Pezzoli, Fabio Massimo; Falciglia, Francesco (Frontiers in Surgery, 2025)
BackgroundRadius and ulna fractures are very common in the pediatric population. Despite the use of pinning through the growth plate, which was proposed in the past and is still being used to treat these fractures, an instrumental validation to define this procedure as safe has not yet been done. Because of this, in the absence of reliable data regarding the passage of fixation devices through the growth plate, most surgical techniques used for treating radius and ulna fractures are based on absolute respect for the growth cartilage. We conducted an MRI pilot study to evaluate the presence of any growth disturbances, bone bridge formation across the physis, or premature closure of the cartilage, to verify the correlation between wire diameter and the percentage of lesions tolerated by the growth plate and to confirm the safety of the trans-physeal pinning procedure. To specifically avoid the wrist fracture healing process near the growth plate as possible bias of the study, we enrolled only patients with mid-shaft forearm fractures.Materials and methodsWe evaluated 26 patients with diaphyseal forearm fractures who underwent intramedullary percutaneous transphyseal fixation of the distal radius with a Kirschner wire. Intramedullary K-wire and plaster cast were removed, without a second surgery or anesthesia, about 35-40 days after surgery. A clinical and radiographic evaluation was performed at 1, 3, 6 and 12 months from surgery. We conducted a comparative MRI evaluation of both wrists 12 months after the removal of the K-wire to exclude any growth plate damage related to the passage of the wire through it.Resultsclinical data underlined excellent results in most patients. Radiographic healing was achieved in all cases at three months. No significative cartilage disturbances related to the procedure were found in any patient. An asymmetrical bridge that did not correspond to the wire position was found in some older patients, probably related to the initial phase of the growth plate closure process.ConclusionThis study demonstrates that the percutaneous trans-physeal technique could become a valid alternative to the standard method, offering a rapid learning curve, shorter surgical times, and reduced healthcare costs.